IMPLEMENTASI KEBIJAKAN PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA (BSPS) TAHUN 2024 DI DINAS PERUMAHAN RAKYAT DAN KAWASAN PERMUKIMAN DAN PERTANAHAN KOTA BITUNG - Delano Mapahena; Agustinus Pati; Welly Waworundeng (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study aims to analyze the implementation of the 2024 Self-Help Housing Stimulant Assistance Program (BSPS) policy at the Bitung City Public Housing, Settlement Areas and Land Agency. Government assistance for low-income communities to encourage and increase self-reliance in improving the quality of homes and building new homes along with infrastructure, facilities, and public utilities is self-help housing stimulant assistance, hereinafter abbreviated as BSPS. In connection with carrying out development, the community must prepare their own resources, because this assistance is realized in the form of goods, to realize the building of the house the community must be self-help. The adequacy of area, quality, and health that must be met by a house building are the requirements for livable standards. The unfulfilled need for livable housing for low-income communities is the government's responsibility. In accordance with Law Number 1 of 2011 which states that the government and local governments need to provide ease of obtaining housing for low-income communities through a gradual housing development planning program in the form of providing easy financing and/or construction of infrastructure, facilities, and public utilities in residential areas. This study uses qualitative research methods. Using the Policy Implementation theory from Van Meter and Van Horn, the research results show that the implementation of the self-help housing stimulus assistance program is running well, but the level of public understanding is still lacking.